2020
DOI: 10.1371/journal.pone.0237772
|View full text |Cite
|
Sign up to set email alerts
|

Substance use service availability in HIV treatment programs: Data from the global IeDEA consortium, 2014-2015 and 2017

Abstract: ¶ Complete membership of the IeDEA Consortium can be found in the Supporting Information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…With work in progress for 11 papers addressing gaps in the literature, IeDEA's 2020 site assessment survey promises to generate more scientific productivity than IeDEA's prior consortium-wide general site assessment surveys [2][3][4] and specialized surveys focused on specific patient populations (e.g., pediatrics, pregnant and postpartum women) [10] and areas of service delivery (e.g., tuberculosis, cancer, mental health disorders, etc.) [11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…With work in progress for 11 papers addressing gaps in the literature, IeDEA's 2020 site assessment survey promises to generate more scientific productivity than IeDEA's prior consortium-wide general site assessment surveys [2][3][4] and specialized surveys focused on specific patient populations (e.g., pediatrics, pregnant and postpartum women) [10] and areas of service delivery (e.g., tuberculosis, cancer, mental health disorders, etc.) [11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly important, as there are overlapping risk contexts (Belenko et al, 2004;Hammett et al, 2002;Spaulding et al, 2002) among women involved in criminal justice systems, with one risk behavior (e.g., substance use) increasing the likelihood for others (e.g., HIV and STIs; intimate partner violence; unintended and high-risk pregnancies (Clarke et al, 2006;Crandall et al, 2003;El-Bassel et al, 2010Elkbuli et al, 2019). Research has established that professional treatment in one of these areas can lead to improvement in other areas (e.g., substance use treatment improving intimate partner violence outcomes) (Murphy & Ting, 2010;Parcesepe et al, 2020), but these current findings suggest that even informal methods of support in one area have the potential to impact other areas of health.…”
Section: Discussionmentioning
confidence: 99%
“…We feel the relatively low screening rates for depression and substance use in HIV clinical settings in the region are likely reflective of a general lack of resources dedicated to addressing mental health and substance use issues across all settings and populations in the region, and related to this, limited capacity of health care workers and health systems to support the delivery of such services [ 22 ]. The same global analysis reported on-site management of substance use disorders in 57%, and another global analysis noted substantial gaps persist in the integration of substance use services into HIV care settings, particularly in resource-constrained settings [ 48 ]. A study in Malaysia published in 2020, found that over 80% of adult PLHIV with prevalent psychiatric symptoms had not previously been recognized clinically, and that only 32% of participants with severe mental health symptoms received a psychiatric referral [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The limited research on approaches to integrating HIV, mental health and substance use services in the region are likely related to a lack of implementation research capacities in the region, and the relatively recent emergence of implementation research as a priority research discipline in the region. Indeed, the importance of implementation research to inform the integration, adaptation or scale-up of mental health or substance use services within HIV care in Asian or resource-limited settings is increasingly being highlighted [ 48 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%